How Rh surface breaks CO2 molecules under ambient pressure - Jeongjin Kim (Nature Portfolio, 2020)
Direct observation of carbon dioxide dissociation provides an origin of catalytic conversion for industrial chemical reactions. Here, the authors reveal their molecular interactions on the rhodium catalyst at near-ambient pressure by interface science techniques and computational calculations.